Macli-ing Dulag: Kalinga Chief Defender of the Cordillera - Roldan, Suzanna R. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
Book review of  Doyo, Ma. Ceres P. 2015. Macli-ing Dulag: Kalinga Chief Defender of the Cordillera. Quezon City: University of the Philippines Press. 92 pp.